2020
DOI: 10.1038/s41422-020-0309-6
|View full text |Cite
|
Sign up to set email alerts
|

s-HBEGF/SIRT1 circuit-dictated crosstalk between vascular endothelial cells and keratinocytes mediates sorafenib-induced hand–foot skin reaction that can be reversed by nicotinamide

Abstract: Hand-foot skin reaction (HFSR), among the most significant adverse effects of sorafenib, has been limiting the clinical benefits of this frontline drug in treating various malignant tumors. The mechanism underlying such toxicity remains poorly understood, hence the absence of effective intervention strategies. In the present study, we show that vascular endothelial cells are the primary cellular target of sorafenib-induced HFSR wherein soluble heparin-binding epidermal growth factor (s-HBEGF) mediates the cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 77 publications
(103 reference statements)
0
16
0
Order By: Relevance
“…Abnormal expression of matrix metalloproteinases such as MMP1 and MMP3 is known to affect the homeostasis of keratinocytes [ 31 , 32 , 33 ]. In addition, MMP1 and MMP3 can be induced by TNF-α and sorafenib treatment, respectively [ 34 , 35 ]. Moreover, these genes have been shown to be downregulated by NRF2 signaling [ 36 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Abnormal expression of matrix metalloproteinases such as MMP1 and MMP3 is known to affect the homeostasis of keratinocytes [ 31 , 32 , 33 ]. In addition, MMP1 and MMP3 can be induced by TNF-α and sorafenib treatment, respectively [ 34 , 35 ]. Moreover, these genes have been shown to be downregulated by NRF2 signaling [ 36 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The HaCaT cell line used in our studies is the most widely studied keratinocyte cell line. It is capable of proliferating and differentiating and often used for the mechanism studies of skin toxicity. As a continuation of our interest in cutaneous toxicity mechanism study, we sought to investigate the direct effect of different Akt subtypes on keratinocytes by employing HaCaT cells. Stable clones of Akt1, Akt2 or Akt3 silenced HaCaT cells were generated with short hairpin RNA (shRNA).…”
Section: Resultsmentioning
confidence: 99%
“…Other cases of crosstalk between vascular ECs and KCs have been reported [34][35][36] . It was recently shown that soluble heparin-binding epidermal growth factor (s-HBEGF) released from vascular ECs activates the epidermal growth factor receptor (EGFR) on KCs and promotes stabilization of sirtuin 1 (SIRT1), an essential keratinization inducer 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Other cases of crosstalk between vascular ECs and KCs have been reported [34][35][36] . It was recently shown that soluble heparin-binding epidermal growth factor (s-HBEGF) released from vascular ECs activates the epidermal growth factor receptor (EGFR) on KCs and promotes stabilization of sirtuin 1 (SIRT1), an essential keratinization inducer 34 . Although the proliferation of human primary KCs with s-HBEGF recombinant protein was almost unchanged in a cell survival assay, significant increase was detected in the mRNA levels of differentiation markers, corroborating the role of s-HBEGF in facilitating keratinization.…”
Section: Discussionmentioning
confidence: 99%